Recent Innovation and Utility in Digitalization of Banking Services in Vellore District - B. Lavanya, Dr. D.S. Selvakumar (International Journal of Advanced Science and Technology, 2020)
Today each and every aspect of business requires innovation. Banking seems to be the largest service industry that provides vulnerable services to its customers. The implementation of digitalization in banking sector paves the way for attracting more and more customers in private as well as public sector banks. The processes of Innovation in digital transactions are increasing rapidly year after year in banking industry. Hence, digital innovations in banking took place in the form of Internet on Things, Artificial Intelligence, Conversional Chatbots, Virtual reality, biometric technology and cloud computing. The main aim of the study is to identify the digital innovations and utility services in banking sector in Vellore district. This study adopts descriptive research design. The primary and the secondary data were used in the study. Percentage analysis, Correlation and t-test were used as a statistical tool in the study.